Results of the use of natural healing factors of Crimea in the treatment of patients with chronic generalized periodontitis with the background of gastroenterological pathology - S. G. Bezrukov; I. F. Feshchenko; E. I. Belenova; E. A. Tarasenko; V. V. Nikolenko (Эндодонтия Today)
Relevance. Currently, researchers pay close attention to the study of chronic diseases that have a direct or indirect impact on the state of the patient’s dental status. It is known that chronic inflammatory diseases of the oral organs are, often simultaneously, permanent foci of infection that affect the state of other systems and organs. The general list of such diseases includes: chronic gingivitis, chronic generalized periodontitis, glossitis, gingivostomatitis.Aim. The aim of the study was to study the effectiveness of complex conservative therapy, including natural therapeutic factors of Crimea, in patients with chronic inflammatory diseases of the oral organs, occurring against the background of somatic pathology.Materials and methods. The objects of the study were periodontal tissues in 70 people with chronic generalized periodontitis (CGP) and gingivostomatitis, occurring against the background of gastrointestinal (GI) diseases.Results. The results obtained indicate that complex treatment with local application of hydrotherapy named “PhytoBiol” and thermal Saka mineral water (in a dilution of 1:4), combined with periodontal dressings according to the recipe proposed by us, cause persistent remission of these diseases, contribute to the improvement of periodontal tissues and oral mucosa. Thus, complex treatment of inflammatory diseases of periodontal tissues in patients in the main group (n = 35) led to long-term remission in 82.33% of cases, while in the control group the result was 69.5% (at p < 0.05).Conclusions. The positive results, which were obtained, give grounds to recommend the proposed complex of treatment and prevention of exacerbations of this chronic disease for use in practical health care.